2010
DOI: 10.1143/jjap.49.01ab14
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Gate Insulators of Polymers and SiO2in Transport Properties of p- and n-Type Organic Field-Effect Transistors

Abstract: Field-effect mobilities and threshold voltages in organic field-effect transistors (OFETs) were studied to elucidate the difference of the OFETs performance between Si/SiO 2 and flexible polymer substrates. The polymer OFETs were built on poly(ethylene naphthalate) (PEN) film as the substrate with polyimide (PI) as the gate-insulators. Pentacene and N,N 0 -ditridecylperylene-3,4,9,10-tetracarboxylicdiimide (PTCDI-C 13 ) were employed as p-and n-type semiconductors. The n-type OFET on polymer substrates exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The distribution of mobility ( a ) and operating voltage ( b ) of OTFTs based on polyimide as dielectrics in the ref. 24 36 and this work …”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The distribution of mobility ( a ) and operating voltage ( b ) of OTFTs based on polyimide as dielectrics in the ref. 24 36 and this work …”
Section: Resultsmentioning
confidence: 78%
“…2d ). Theoretically, in the imidization process, stretching vibration of carbon-carbon double bond (C=C, 1500 cm −1 ) of benzene ring keeps unchanged, therefore the ratio of peak intensity between ~1375 (C–N–C) and 1500 cm −1 (C=C) is generally used to calculate the degree of the imidization 36 38 . By defining 300 °C annealing resulting in complete imidization (100%), then the imidization degree (200 °C) of copolymer was calculated to be 89%, which further confirmed that polar groups (−COOH/−CONH) existed in the copolymer.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted in this study that the n-type devices on flexible substrates exhibited better mobility and lower V T in contrast to those on Si/SiO 2 . On the contrary, p-type devices on Si/SiO 2 substrates were better than those on the flexible substrates [130].…”
Section: Materials Selection Criteria For Os Devicesmentioning
confidence: 90%
“…The performance comparison of OFETs using Si/SiO 2 and flexible polymer substrates was made [130] in terms of mobility and V T . PEN substrate, polyimide dielectric along with pentacene and PTCDI-C 13 as p and n-type semiconductors were used in these experimental OFET devices.…”
Section: Materials Selection Criteria For Os Devicesmentioning
confidence: 99%
“…For flexible devices, C ins was directly measured by the capacitance of Au/ PMMA/Au fabricated on the same substrate, 8 being around 6 nF cm ¹2 . Ionization potential was evaluated in a BHT-TT film.…”
mentioning
confidence: 99%